Edukasi Perawatan Fiberglass Pada Kapal Long Boat Menggunakan Metode Material Komposit Di Pulau Rutum, Kepulauan Ayau, Raja Ampat - Boby Wisely Ziliwu; Rezza Ruzuqi; Bagas Prakoso; Marcelinus P. Saptono (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The diversity of Indonesia's wealth is marked by the number of small islands, natural resources are still unexplored. The West Papua province has the outermost islands, one of which is Rutum Island. Rutum Island is one of the islands in the Ayau Archipelago (West Papua Province). The people of Rutum, mostly use boats that are less than 15 meters in size to carry out fishing activities and so on. Most of the ships are made of Fiberglass reinforced Polymer Composite Material. The condition of the area is surrounded by coral reefs. So many ships were damaged. The ship maintenance process is very difficult, because the condition of the area is far from the city center. In general, the ship maintenance process adjusts to the level of damage to the ship. On the island of Rutum, the ship's damage to the lower hull suffered loss of the ship's walls. The use of appropriate standards, needs to be applied so that the ship provides a sense of security and comfort for users. The method used in this activity is the material compossit method. Then patch the damaged parts with a resin-catalyst alloy reinforced with fiberglass Woven Roven 600 and Chopped Strand Mat 450. The number and variety of layers are adjusted according to the reference. The results obtained show a strong patch. However, if viewed from the damage, there needs to be additional repairs. This is because, the main material of the ship is already porous due to sea water.